PERAN TRANSPARANSI DIGITAL DALAM MENINGKATKAN AKUNTABILITAS PUBLIK: STUDI PENGELOLAAN INFORMASI PUBLIK PADA WEBSITE RESMI PEMERINTAH DAERAH - I Nyoman Ade Saputra; Raihan A. Hanasi; Sri Rosdiyanti Dalila; Deswita Maharani Poluan; Citra Wati Yunus; Refais Andrean Korompot (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2026)
The use of official local government websites as a channel for disclosing public information is one way that the advancement of information and communication technology has fueled the digital transformation of governance. Due to Indonesia's high internet usage, local governments must make public information readily available, quick, and transparent in order to uphold the values of public accountability and good governance. However, there are still a number of challenges to the adoption of digital-based public information disclosure, including subpar information updates, inconsistent website management, and a lack of interactive public communication services. The purpose of this study is to examine how public information management on official local government websites can enhance public accountability through digital transparency. This study combines descriptive techniques with a qualitative methodology. Observation of local government websites, paperwork, and literature reviews were used as data gathering methods. Data reduction, data display, and conclusion drawing are all part of the interactive paradigm used in data analysis. The findings demonstrate the importance of digital transparency via local government websites in promoting public information disclosure and enhancing local government accountability. Websites run by local governments have been used to disseminate information about public services, government activity reports, and government programs. However, due to the influence of poor public information management, a lack of human resources, and poor public communication feature optimization, the deployment of digital transparency has not been operating at its best. This study suggests that the government's commitment to handling public information in an open, accurate, and sustainable manner is just as important to the success of digital transparency as the presence of a local government website.